Assessment of drug utilization among geriatric patients based on defined daily dose concept in a rural tertiary care teaching hospital - Padmavathi, K.; Raaj, S. A. Arun; Subash, S.; Dhanapal, C. K.; Periasamy, S. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objectives of the study were to use the anatomical therapeutic chemical classification (ATC) /defined daily dose (DDD) concept to study the drug utilization pattern in geriatric patients in a rural tertiary care teaching hospital. Methods: An observational study was conducted at Rajah Muthiah Medical College Hospital (OPD and IPD) over a period of six months from November 2018 to April 2019. The data was collected from 204 patients using specially designed data collection form. The patients were selected based on inclusion and exclusion criteria. Results: A total of 204 patients were included in this study. The study population consisting of males 130 (63.7%) and females 74 (36.2%). Diseases related to the cardiovascular system 67 (32.84%) were the most common cause for the geriatric patients to attend the hospital, followed by surgical diseases 47 (23.03%), Oncological diseases 2 (0.98%) were the least frequency encountered. The average number of drugs prescribed per prescription was 8.79. Out of 1795 drugs prescribed, 60.86% of drugs were prescribed in generic form, and 39.14% were prescribed in brand name. The study analysed that 71.25% of drugs prescribed were from essential drug list (EDL) 2016-2018. Number of prescriptions with an injection was 74.04%. Paracetamol (N02B01) was the most frequently prescribed drug, followed by Amlodipine (C08CA01), Dexamethasone (H02AB02), Clopidogrel (B01AC04), Ferrous sulfate (B03AA07), Acetylsalicylic acid (B01AC06), Hydrocortisone (H02AB09), Tamsulosin (G04CA02), Atorvastatin (C10AA05), Furosemide (C03CA01). Conclusions: Drug utilization study can help in evaluating the quality of care given to the geriatric patients and promote rational use of medicines.